Utilization of the limit equilibrium and finite element methods for the stability analysis of the slope debris: An example of the Kalebasi District (NE Turkey) - Alemdag, Selcuk; Kaya, Ayberk; Karadag, Mustafa; Gurocak, Zulfu; Bulut, Fikri (Pergamon-Elsevier Science Ltd, 2015)
The stability of the slope debris in residential area of the Kalebasi District (Ozkurtun-Gumushane) was investigated using the Limit Equilibrium (LE) and Finite Element Shear-Strength Reduction (FE-SSR) methods. Along the survey lines, four trial pits were dug and fourteen boreholes having a total length of 345 m were drilled. Also, seismic refraction studies were conducted along the five lines. According to the field studies, thickness of the slope debris covering the 98 ha of the study area varies between 1 and 36 m. To determine the physical and shear strength properties of the slope debris, undisturbed samples were taken from the trial pits. As a result of the laboratory tests, soil categories of the debris were found to be as Clayey Sand (SC), Silty Sand (SM) and Low Plasticity Clay (CL). The deformation-controlled shear box tests were carried out to determine the shear strength parameters of the slope debris. According to these tests it was found that the peak cohesion and peak friction angle varies between 2.63-16.35 kN/m(2) and 20-27 degrees, respectively. Stability analyses were performed using the obtained data from field and laboratory investigations in the Slide v5.0 and Phase(2) v6.0 software programs and results were compared. In LE stability analyses, the factor of safety (FOS) of survey lines were found to be as 1.44, 1.80, 1.96, and 1.72; however for the FE-SSR method they were determined as 1.39, 1.72, 1.59, and 1.58, respectively. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Limit equilibrium analysis; Slope debris; Shear strength reduction method; Stability analysis